Modifications of probabilistic models of states evolution for reliability analysis of district heating systems - Ivan Postnikov; Valery Stennikov (Energy Reports, 2020)
The analysis and synthesis of reliability of energy systems, particularly district heating systems (DHS), is based on probabilistic modeling of different system states and events connecting these states (usually, these are failures and restoration of system components). The paper deals with the problem of modeling the probabilities of DHS states based on a Markov random process under conditions that can be characteristic for actual systems: joint and dependent failures of several components. For this purpose, it probabilistic models of the evolution of events in DHS taking into account non-ordinary events and dependent between them are developed. The methodology is based on the theory of Markov random processes and the basic laws of probability theory. The formation principles of developed models are illustrated by the state graphs. Numerical studies were carried out, the results of which allows determine some properties and application limits of developed models.
Keywords: 330; Availability factor; District heating system; Failure and restoration rates; Markov random processes; Non-ordinary and depending events; Probabilistic models; Rate of transition; Reliability analysis; Reliability indices; States evolution